THE ROLE OF POLITICAL PARTIES IN THE DEVELOPMENT OF POLITICAL PROCESSES (Conferencea, 2024)
Modern political life, and especially elections, are unimaginable without political parties. Political parties the main carriers of interests in society are the political system. Without parties, neither the electoral process, nor the formation of a political elite, nor the implementation of any political course, which state bodies carry out in practice, is possible. Therefore, if we want to better understand the mechanisms of functioning of modern democracy, it is inconceivable that this can be done without studying parties. Modern representative democracy was practically formed together with parties, or rather, the formation of representative democracy gave rise to the need for the existence of political parties. Due to the fact that in representative democracy, people no longer directly participate in governance, they create organizations through which they can present and protect their interests. Therefore, the need to create political parties arose. “According to Edmund Burke, a political party is an organization formed by individuals who have more or less common ideological and worldview views.” [Burroughs, G. et al. (2020), Democracy and Citizenship, Tbilisi, pp. 93-94].